Definición de las preferencias de lectores del diario el universo entre su versión impresa versus digital - Báscones Álvarez, Verónica Irene (2016)
This project was carried out in order to define the preference of the Universe Journal readers between its print and digital version, when informed, living in a world where technology is advancing by leaps and bounds daily. For this survey 160 people were held between 18 and 65 years in the Citadel La Saiba, south of Guayaquil, between apples A - B - C and N-2 Block. It also takes into account an interview with Ing. Ruthsbel Tambo, New Media Coordinator morning, quotes, articles, and other information gathered to be placed…..